Effect of Anticipated Fear, Risk Perception and Response Efficacy on Travel Intention - Vishwakarma, Pankaj (ASEAN Journal on Hospitality and Tourism, 2024)
The Covid-19 outbreak has impacted the tourism industry worldwide. It has also affected how travelers used to travel. The present study investigates travelers’ behavior grounded on the Theory of Planned Behavior (TPB). The study incorporated a new concept of risk perception of Covid-19, anticipated fear and response efficacy, and examined travel behavior across two groups of people. The first group desires to travel a short distance while the other desires to travel a far distance destination. The work also investigates how these two groups are different in their travel intention. The data collected from 507 individuals have been utilized for the analysis using structural equation modeling. Overall, the risk perception of Covid-19 is found to have a vital and significant impact on individuals’ travel intention, followed by one’s response efficacy towards it. Further, the two groups are found different at the model level and also across a few paths  . The findings will help DMOs and the government curate strategies in case of a similar scenario (e.g., an epidemic).